Design of Nutrition Consultation Service Application at the Teaching Factory Nutrition Care Center of Politeknik Negeri Jember - Roziqin, Mochammad Choirur; Selviyanti, Erna; Putra, Dony Setiawan Hendyca (International Journal of Health and Information System, 2024)
A website is one of the digital healthcare service platforms that can be accessed through smartphones, facilitating the connection between healthcare providers, nutritionists, and the public for healthcare services. The Teaching Factory Nutrition Care Center is a nutrition service center managed by healthcare providers from the Department of Health at Politeknik Negeri Jember. Clients visiting the center can receive health consultations related to tracking their health, adopting a healthy diet, daily nutrition consultations, issues related to stunting in infants and toddlers, as well as consultations for pregnant mothers. The identified problem is the lack of a profile website that provides information to the public and the manual booking of consultations through staff or via WhatsApp. Result: A design proposal for a web-based application is suggested as a promotional and informational platform. It should have features including an information menu for healthy diets related to various diseases, a schedule of nutrition counselors, an online chat with nutrition counselors, and information related to articles or news about health and nutrition. The design process followed the waterfall method up to the design stage. The website design has been successfully completed.